GAME ON! JOYFUL LEARNING AS A BOOSTER FOR MOTIVATION AND ACTIVE LEARNING IN ISLAMIC RELIGIOUS EDUCATION FOR NINTH GRADE STUDENTS AT SMP NEGERI 2 SUMBER, CIREBON REGENCY - Maolla, Nur Wakhdatun; Jamali, Jamali; Affandi, Akhmad; Nuryadien, Mahbub (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the effectiveness of game-based Joyful Learning in enhancing students’ motivation and learning activeness in Islamic Religious Education (PAI) at SMP Negeri 2 Sumber, Cirebon Regency. A quantitative approach with a descriptive-associative design was employed to measure the effect of Game-Based Learning on both dependent variables. The research sample consisted of 76 ninth-grade students selected through purposive sampling. Data were collected using questionnaires, observations, and open interviews, and analyzed using MANOVA with SPSS version 25.0. The results revealed that game-based Joyful Learning had a significant and strong effect on students’ learning motivation (η² = 0.730) and activeness (η² = 0.754). Multivariate analysis further confirmed a simultaneous significant effect (Sig. = 0.000) between both variables. The approach successfully fostered an interactive, enjoyable, and meaningful learning environment, encouraging students’ cognitive, affective, and social engagement. This study concludes that game-based Joyful Learning is an effective strategy to enhance the quality of Islamic Religious Education in the digital era.